Essential statistics in business and economics - Doane, David P. (McGraw-Hill/Irwin, 2008)
All statistical concepts are illustrated with applied examples immediately upon introduction. Modern computing tools and applications are introduced, and the text maintains a strong focus on presenting statistical concepts as applied in business--as opposed to providing programming methods used to find a mathematical solution. Interpretation of results is heavily emphasized, enabling students to take full advantage of Excel to develop and drive problem-solving skills.